COVID-19 vaccine safety during pregnancy and breastfeeding in women with autoimmune diseases: results from the COVAD study. - Andreoli, Laura; Lini, Daniele; Schreiber, Karen; Parodis, Ioannis; Sen, Parikshit; Ravichandran, Naveen; Day, Jessica; Joshi, Mrudula; Jagtap, Kshitij; Nune, Arvind; Nikiphorou, Elena; Agarwal, Vishwesh; et al. (Rheumatology, 2024)
OBJECTIVES: We investigated coronavirus disease 2019 (COVID-19) vaccine safety in pregnant and breastfeeding women with autoimmune diseases (AID) in the COVID-19 Vaccination in Autoimmune Diseases (COVAD) study. METHODS: Delayed-onset (>7 days) vaccine-related adverse events (AE), disease flares and AID-related treatment modifications were analysed upon diagnosis of AID vs healthy controls (HC) and the pregnancy/breastfeeding status at the time of at least one dose of vaccine. RESULTS: Among the 9201 participants to the self-administered online survey, 6787 (73.8%) were women. Forty pregnant and 52 breastfeeding patients with AID were identified, of whom the majority had received at least one dose of COVID-19 vaccine (100% and 96.2%, respectively). AE were reported significantly more frequently in pregnant than in non-pregnant patients (overall AE 45% vs 26%, P = 0.01; minor AE 40% vs 25.9%, P = 0.03; major AE 17.5% vs 4.6%, P < 0.01), but no difference was found in comparison with pregnant HC. No difference was observed between breastfeeding patients and HC with respect to AE. Post-vaccination disease flares were reported by 17.5% of pregnant and 20% of breastfeeding patients, and by 18.3% of age- and disease-matched non-pregnant and non-breastfeeding patients (n = 262). All pregnant/breastfeeding patients who experienced a disease flare were managed with glucocorticoids; 28.6% and 20% of them required initiation or change in immunosuppressants, respectively. CONCLUSION: This study provides reassuring insights into the safety of COVID-19 vaccines administered to women with AID during the gestational and post-partum periods, helping overcome hesitant attitudes, as the benefits for the mother and for the fetus by passive immunization appear to outweigh potential risks.
EVALuna2:544055